Implementation of a Supply chain Management System Blockchain-Based in Red Onion Farming - Nabila, Mira; Alzami, Farrikh; Megantara, Rama Aria; Tananto, Fikri Firdaus; Syafrudin, Hasan Aminda; Handoko, L. Budi; Umam, Chaerul (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2023)
Red Onions are a horticultural commodity belonging to the spice vegetable group and an important role for economy of the Indonesian people. In red onion farming there have a problem of price fluctuations which result in an uneven and less transparent distribution of red onions yields, thus affecting both consumers and producers. To answer these problems, we designed a system to maintain and store red onion harvest data for farmers, collectors, distributors, and retailers in the form of a blockchain-based supply chain system. This system can maintain the validity of transactions in the supply chain of red onion farming with a private blockchain with Hyperledger Fabric. Then the data on the blockchain system will be displayed through the Hyperledger Explorer website. This system already passed the Black Box Testing system. From the research and testing of the system that has been made, this system can help the red onion farming to maintain the validity of transactions in the supply chain management.